Hubungan Peran Keluarga Pasien Diabetes Mellitus Dengan Pelaksanaan Diet 3j Di Puskesmas Jatiroto Kabupaten Lumajang - Zainal Abidin; Dodik Hartono; Siswa Aini (PROFESSIONAL HEALTH JOURNAL, 2023)
Diabetes mellitus is a chronic disease characterized by high levels of sugar (glucose) in the blood. One of them can be minimized by implementing the 3J diet, to achieve the effective implementation of the 3J diet, the role of the family is needed in its implementation. This study aims to determine the relationship between the role of the family of diabetes mellitus patients with the implementation of the 3J diet In Community Health Center Lumajang. This type of research is correlational analytic with a cross sectional approach. Population All patients with diabetes mellitus at the Jatiroto Public Health Center were 33 people, the determination of the sample using the accidental sampling technique that met the criteria was 31 respondents. The instrument used was a questionnaire on family roles and the implementation of the 3J diet. Data processing with Editing, Coding, Scoring and Tabulating processes, then analyzed using the Spearman Rank Test. The results of this study indicted that the group with the most family roles is low as many as 16 respondents (51.6%) the group implementing the 3J diet is mostly good as many as 12 respondents (38.7%), the results of the analysis test using the Spearman Rank Test there is a relationship between family roles patients with diabetes mellitus with the implementation of the 3J diet In Community Health Center Lumajang (r-valeu= 0.000 < = 0.05). One of the roles of the family that can be done in the care of patients with diabetes mellitus is the emphasis on implementing the 3J diet that has been made by health workers, namely the right meal schedule, the right amount of food, and the right type of food eaten. Implementation of the 3J diet is very important to improve blood sugar levels, and minimize the risk of complications. Keywords: Diabetes mellitus, Family Role, Implementation of the 3J Diet.